On a Class of Semicommutative Rings - Özen, Tahire; Agayev, Nazım; Harmancı, Abdullah (Department of Mathematics, Kyungpook National University, 2011)
In this paper, a generalization of the class of semicommutative rings is inves- tigated. A ring R is called central semicommutative if for any a; b 2 R, ab = 0 implies arb is a central element of R for each r 2 R. We prove that some results on semicommutative rings can be extended to central semicommutative rings for this general settings.